2006
DOI: 10.1128/cvi.13.3.319-328.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Quercetin Inhibits Proinflammatory Cytokine (Tumor Necrosis Factor Alpha) Gene Expression in Normal Peripheral Blood Mononuclear Cells via Modulation of the NF-κβ System

Abstract: The flavonoids comprise a large class of low-molecular-weight plant metabolites ubiquitously distributed in food plants. These dietary antioxidants exert significant antitumor, antiallergic, and anti-inflammatory effects. The molecular mechanisms of their biological effects remain to be clearly understood. We investigated the anti-inflammatory potentials of a safe, common dietary flavonoid component, quercetin, for its ability to modulate the production and gene expression of the proinflammatory cytokine tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
241
6
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(267 citation statements)
references
References 41 publications
13
241
6
7
Order By: Relevance
“…Those results are consistent with the report that quercetin lowers the level of proinflammatory gene expression as a consequence of oxidative stress and different stimuli (Chuammitri et al, 2015;Valerio et al, 2009). Accordingly, the antiinflammatory action of quercetin on TNF-α is dosedependent manner (Nair et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Those results are consistent with the report that quercetin lowers the level of proinflammatory gene expression as a consequence of oxidative stress and different stimuli (Chuammitri et al, 2015;Valerio et al, 2009). Accordingly, the antiinflammatory action of quercetin on TNF-α is dosedependent manner (Nair et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon may be controlled by the transcription factor NF-κB. Many reports have mentioned that quercetin exerts its modulatory effects by reduction of pro-inflammatory genes through NF-κB inactivation (Boesch-Saadatmandi et al, 2011;Cho et al, 2003;Nair et al, 2006). From previous studies, quercetin inhibits the production of many proinflammatory cytokines, including IL-1β and TNF, the findings from the present work suggest that quercetin may be able to modulate the immune response via the NF-κB pathway.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…47 Recent research also confirmed that quercetin as one of active compound from M. fragrans can inhibit various cytokines including TNF-α, IL-6, and IL-1β. 15,16,31,48,49 NO plays a significant role in host immune defense, vascular regulation, neurotransmission, and other system in normal condition. Overproduction of inducible NO Synthase (iNOS) is especially related to various human diseases including inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, the most commonly occuring flavonoid is an excellent antioxidant that is also suggested to possess other beneficial activities. 15,16 The aim of this research is to determine anti-inflammatory potential of M. fragrans seed (Nutmeg) ethanolic extract and pure quercetin extract from M. fragrans on LPS stimulated-murine macrophage cell line (RAW 264.7).…”
Section: Introductionmentioning
confidence: 99%